Ageism and the Older Worker: A Scoping Review. (12th January 2017) - Harris, Kelly; Krygsman, Sarah; Waschenko, Jessica; Laliberte Rudman, Debbie
Abstract: Purpose of the Study: Given the policy shifts toward extended work lives, it is critically important to address barriers that older workers may face in attaining and maintaining satisfactory work. This article presents a scoping review of research addressing ageism and its implications for the employment experiences and opportunities of older workers. Design and Methods: The five-step scoping review process outlined by Arksey and O'Malley was followed. The data set included 43 research articles. Results: The majority of articles were cross-sectional quantitative surveys, and various types of study participants (older workers, human resource personnel/manager, employers, younger workers, undergraduate students) were included. Four main themes, representing key research emphases, were identified: stereotypes and perceptions of older workers; intended behavior toward older workers; reported behavior toward older workers; and older workers' negotiation of ageism. Implications: Existing research provides a foundational evidence base for the existence of ageist stereotypes and perceptions about older workers and has begun to demonstrate implications in relation to intended behaviors and, to a lesser extent, actual behaviors toward older workers. A few studies have explored how aging workers attempt to negotiate ageism. Further research that extends beyond cross-sectional surveys is required to achieve more complex understandings of the implications of ageism and inform policies and practices that work against ageism.